MODERNISASI ADMINISTRASI PENDIDIKAN: ANALISIS KUALITAS LAYANAN DATA BERBASIS EMIS DI KANTOR KEMENTERIAN AGAMA - Fauziah Noor Ilmi An-Nabhani; Hinggil Permana; Abdul Kosim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The modernization of data governance through the Education Management Information System (EMIS) has become a key strategy for improving public service quality within the Ministry of Religious Affairs. However, its implementation often faces technical and system integration challenges. This study aims to analyze the quality of EMIS-based data services, coordination workflows, and the obstacles encountered by Islamic Education Teachers (GPAI). A descriptive qualitative method with a case study approach was employed at the Office of the Ministry of Religious Affairs of Karawang Regency. Data were collected through document analysis and in-depth interviews with Islamic Education teachers, EMIS operators, and the Head of the Islamic Education Section. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that EMIS has contributed significantly to the transformation of administrative processes from manual to integrated digital services. The system has improved transparency, data accessibility, and the validity of teacher certification and personnel records. Effective coordination among stakeholders has also supported the implementation of EMIS-based services. Nevertheless, several challenges remain, including central server congestion during peak usage periods, extended system maintenance, unstable internet connectivity, and data synchronization issues with the Basic Education Data System (Dapodik). These obstacles occasionally affect the efficiency and reliability of data management services. In conclusion, EMIS has enhanced bureaucratic efficiency and strengthened educational data governance. However, continuous technical improvements and stronger system integration are required to ensure consistent, reliable, and high-quality data services for all users.